Application of molecular dynamics simulation: A case study to estimate wettability - Khosravi, V. (Springer Science and Business Media Deutschland GmbH, 2020)
Enhanced oil recovery (EOR) has always been a significant pillar in the oil industry, and lots of laboratory studies have been conducted for this technology. However, experimental research in EOR encounters several problems such as expensive materials and equipment, and long-term duration of measurements that could take from weeks to years. In this backdrop, molecular dynamics simulation (MDS) appears to be an efficient complementary method that can be used for first-order approximation once it is validated. The objective of this work is to evaluate the efficacy of molecular dynamics (MD) for the understanding of wetting condition of a given rock/fluid system by calculating the free energy which could yield contact angles (a measure of wettability). The interaction between polyethylene surface and n-decane oil as the first system as well as polyethylene surface and cyclohexane oil as the second system was simulated by MDS, and the total free energies were calculated to be â7.515 (kcal/mol) and â1.872 (kcal/mol), respectively. Contact angles were calculated from MDS and computed 15.4 degrees for the first, and 28.6 degrees for the second system. The deviation for n-decane was 3.1-degree, and cyclohexane was 0.4-degree on the same surface compared to the published results. Data shows that the MDS is a reliable method for the first-order estimation of wettability determination for the purpose of initial screening and optimization of EOR processes relying upon wettability alteration. Â© Springer Nature Singapore Pte Ltd 2020.